Epidemiological profile of visceral leishmaniasis in the city of Redenção- PA (Research, Society and Development, 2023)
Objective: To analyze and describe the profile of people affected by VL in a municipality in the southeast of the state of Pará from 2010 to 2020. Methods: This is an epidemiological, descriptive survey, with a quantitative approach, using secondary data from the platform information technology department of the Unified Health System in Brazil (DATASUS), and the Notifiable Diseases Information System (SINAN), derived from compulsory notifications of reported VL cases. Results: In the analyzed period, 419 cases of VL were registered. The year with the highest incidence of cases was 2014 with 79 reported. In addition, the most affected age group was 20 to 39 years and the predominant race was brown, with a prevalence of the disease in males. In addition, 376 cases occurred in the urban area and 373 patients were cured. Conclusion: In view of the data collected, it can be inferred that VL, in the municipality of Redenção, presents only 89% of cure, and it is important to expand further studies in order to reduce the incidence of this pathology.